Proceedings of the Thirtieth International Joint Conference on Artificial Intelligence 2021
DOI: 10.24963/ijcai.2021/214
|View full text |Cite
|
Sign up to set email alerts
|

Masked Label Prediction: Unified Message Passing Model for Semi-Supervised Classification

Abstract: Graph neural network (GNN) and label propagation algorithm (LPA) are both message passing algorithms, which have achieved superior performance in semi-supervised classification. GNN performs feature propagation by a neural network to make predictions, while LPA uses label propagation across graph adjacency matrix to get results. However, there is still no effective way to directly combine these two kinds of algorithms. To address this issue, we propose a novel Unified Message Passaging Model (UniMP) that can i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
107
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(147 citation statements)
references
References 0 publications
0
107
0
Order By: Relevance
“…Recent works use Laplacian spectra, node degrees, and shortestpath lengths as positional encodings to expand attention to all nodes (Kreuzer et al, 2021;Dwivedi and Bresson, 2021;Rong et al, 2020;Ying et al, 2021). Several works also adapt attention mechanisms to GNNs (Yun et al, 2019;Cai and Lam, 2019;Hu et al, 2020;Baek et al, 2021;Veličković et al, 2018;Wang et al, 2021b;Zhang et al, 2020;Shi et al, 2021).…”
Section: Related Workmentioning
confidence: 99%
“…Recent works use Laplacian spectra, node degrees, and shortestpath lengths as positional encodings to expand attention to all nodes (Kreuzer et al, 2021;Dwivedi and Bresson, 2021;Rong et al, 2020;Ying et al, 2021). Several works also adapt attention mechanisms to GNNs (Yun et al, 2019;Cai and Lam, 2019;Hu et al, 2020;Baek et al, 2021;Veličković et al, 2018;Wang et al, 2021b;Zhang et al, 2020;Shi et al, 2021).…”
Section: Related Workmentioning
confidence: 99%
“…Experimental results of the Unified Message Passaging model (UniMP) [33] have shown that considering the label information on neighbors can bring significant improvements to prediction tasks. Therefore, inspired by the label propagation method of UniMP, we constructed a PSN to excavate extra information for the LOS prediction, with the assumption that similar patients would have similar LOS in the network.…”
Section: Patient Similarity Network Constructionmentioning
confidence: 99%
“…For an utterance, the action and intention of the speaker and interactions with other utterances in past, present, and future are crucial to model the context more precisely. Therefore, we construct a pSychological-Knowledge-Aware Interaction Graph (SKAIG) of utterances in a conversation, and then utilize the Graph Transformer (Shi et al, 2021) network to process SKAIG.…”
Section: Conversation-level Encodermentioning
confidence: 99%
“…In addition, we replace the original operation after the attention in Shi et al (2021) to a pointwise feed forward network proposed by Vaswani et al (2017). We denote the final output of the conversation as H L ∈ R N ×du .…”
Section: Graph Transformermentioning
confidence: 99%
See 1 more Smart Citation